Act on Facilitation in the Preparation and Implementation of Housing and Accompanying Investments ("Lex developer") in the light of economic analysis of law - Antczak-Stępniak, Agata; Zaleczna, Magdalena (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
Like many countries in the world, Poland is struggling with a significant housing deficit, especially those available to people with lower incomes. For several years, actions have been taken at the government level to solve this problem. One was adopting the Act on Facilitation in the Preparation and Implementation of Housing and Accompanying Investments ("Lex developer"). The legislator's assumption was to improve the process of building new apartments by lowering the planning and administrative requirements. The study aims to assess whether the new regulations can be call efficient from the point of economic analysis of Law. The authors conducted an ex-post analysis because some years of operation of the new Act allowed for some conclusions of real results of implementation of the Act. The Authors used desk research in form of critical literature analysis, national and local legal acts analysis, comparative analysis, and case studies methods. The authors came to the conclusion that the collected material entitles us to conclude that the analyzed legal act does not meet the accepted criteria of effective law. The authors came to the conclusion that collected material entitles to conclude that the analyzed legal act does not meet the accepted criteria of effective law.